Climate urbanism as critical urban theory. Issue 6 (3rd July 2021) - Castán Broto, Vanesa; Robin, Enora
ABSTRACT: As urban actors engage in climate action, their projects – from urban greening to changes in urban energy systems – reshape not just the urban built environment but also the organization of social life. This new climate urbanism invites to reimagine what it means to be urban in a climate-changed world. We propose the articulation of climate urbanism as a critical theory that both exposes the production of further inequalities associated with urban responses to climate change and provides new radical forms of practice for more progressive urban futures under climate change.